(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Integral condition has been one of the basic apparatuses for different zones of connected arithmetic. In this paper, we audit unique numerical strategies for tackling both direct and nonlinear Fredholm integral equations of second kind. The objective is to classify the chosen techniques and survey their precision and productivity. We talk about difficulties looked by specialists in this field, and we underline the significance of interdisciplinary exertion for propelling the investigation on numerical techniques for fathoming integral equations. In this paper we study about the past studies on Numerical Methods for the Solution of Integral Equations.